Flexible endoscope-assisted evacuation of chronic subdural hematomas - Májovský, Martin; Masopust, Václav; Netuka, David; Beneš, Vladimír (Acta neurochirurgica, 2016)
BACKGROUND: Chronic subdural hematoma (CSDH) is a common neurosurgical condition with an increasing incidence. Standard treatment of CSDHs is surgical evacuation. The objective of this study is to present a modification of standard burr-hole hematoma evacuation using a flexible endoscope and to assess the advantages and risks. METHODS: Prospectively, 34 consecutive patients diagnosed with CSDH were included in the study. Epidemiological, clinical and radiographical data were collected and reviewed. All patients underwent a burr-hole evacuation of CSDH. A flexible endoscope was inserted and subdural space inspected during surgery. The surgeon was looking specifically for the presence of septations, draining catheter position and acute bleeding. RESULTS: Thirty-four patients underwent 37 endoscope-assisted surgeries. Presenting symptoms were hemiparesis (79%), decreased level of consciousness (18%), gait disturbances (15%), headache (12%), aphasia (6%), cognitive disturbances (6%) and epileptic seizure (3%). Average operative time was 43 min, and the average increase in operative time due to the use of the endoscope was 6 min. Recurrence rate was 8.8%, and clinical outcome was favorable (defined as mRS ≤ 2) in 97% of the cases. CONCLUSIONS: To our knowledge, the present cohort of 34 patients is the largest group of patients with CSDH treated using an endoscope. This technique allows decent visualization of the hematoma cavity while retaining the advantages of a minimally invasive approach under a local anesthesia. The main advantages are correct positioning of the catheter under visual control, identification of septations and early detection of cortex or vessel injury during surgery.
Keywords: dospělí; Female; vědomí; trepanace; Adult; ženské pohlaví; endoskopie; Consciousness; Hematoma, Subdural, Chronic; lidé; bolesti hlavy; Subdural Space; pooperační komplikace; Trephining; Aged, 80 and over; drenáž; Drainage; Minimally Invasive Surgical Procedures; chronický subdurální hematom; Male; Postoperative Complications; Aged; Headache; Endoscopy; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; miniinvazivní chirurgické výkony; Middle Aged; subdurální prostor; Humans